PENGARUH PENAMBAHAN PROBIOTIK PADA PAKAN IKAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BIBIT IKAN NILA - As'urin, B; Sulastri, Sulastri (JARI : Jurnal Akuakultur Rawa Indonesia, 2024)
Parrot fish is a type of fish that is easy to cultivate, grows quickly and has the ability to digest food well. One of the factors that must be considered in cultivation is feeding and water quality. One effort that can be made to increase fish growth is by providing probiotics. Therefore, the aim of this research is to determine the effect of adding different probiotics to feed on the growth rate and survival of tilapia fish seedlings. This research used a Completely Randomized (CRD) design with one factor, three treatment levels and three replications. Each treatment was given the addition of probiotics in the amount of P1 10 ml viterna, P2 10 ml EM4 and P3 10 ml molasses. The results of this study show that the addition of probiotics has a significant effect on the growth rate and survival of tilapia fish seeds. The best treatment was P2, with a growth rate of 20.33% and survival of 78.33%. Key words : , , ,